OPERATING CASH FLOW DRIVES PROFIT STABILITY IN INDONESIAN MANUFACTURING - Umam, Rifki Khairul; Tumirin, Tumirin (Journal of Economic and Economic Policy, 2024)
General Background: Profit persistence, reflecting a company’s ability to maintain consistent profits over time, is a crucial indicator of financial stability and long-term performance. Specific Background: In the context of manufacturing companies in the basic materials sector listed on the Indonesia Stock Exchange (IDX) for the period 2022-2023, various financial metrics, such as operating cash flow, company size, and leverage, potentially influence profit persistence. Knowledge Gap: Prior studies have not thoroughly explored the individual and combined effects of these financial variables on profit persistence within this specific sector and timeframe. Aims: This study aims to analyze the influence of operating cash flow, company size, and leverage on profit persistence in manufacturing firms within the basic materials sector listed on the IDX. Results: Utilizing a quantitative approach and multiple linear regression analysis through SPSS 25.0, the study finds that operating cash flow significantly affects profit persistence. In contrast, company size and leverage do not exhibit a significant individual impact on profit persistence. However, collectively, operating cash flow, company size, and leverage do influence profit persistence. Novelty: The study contributes to the existing literature by providing a detailed analysis of how specific financial metrics interact to affect profit persistence, with a focus on a narrowly defined sector and a relatively short observation period. Implications: The findings suggest that while operating cash flow is a critical factor in ensuring profit stability, company size and leverage may not independently influence profit persistence. Future research is recommended to extend the study period and include a broader range of sectors to enhance generalizability and explore additional variables that may impact profit persistence.